The Dual Effect of the BMP9–ALK1 Pathway in Blood Vessels: An Opportunity for Cancer Therapy Improvement? - Blanca Ayuso-Íñigo (MDPI AG, 2021)
The improvement of cancer therapy efficacy, the extension of patient survival and the reduction of adverse side effects are major challenges in cancer research. Targeting blood vessels has been considered a promising strategy in cancer therapy. Since the tumor vasculature is disorganized, leaky and triggers immunosuppression and tumor hypoxia, several strategies have been studied to modify tumor vasculature for cancer therapy improvement. Anti-angiogenesis was first described as a mechanism to prevent the formation of new blood vessels and prevent the oxygen supply to tumor cells, showing numerous limitations. Vascular normalization using low doses of anti-angiogenic drugs was purposed to overcome the limitations of anti-angiogenic therapies. Other strategies such as vascular promotion or the induction of high endothelial venules are being studied now to improve cancer therapy. Bone morphogenetic protein 9 (BMP9) exerts a dual effect through the activin receptor-like kinase 1 (ALK1) receptor in blood vessel maturation or activation phase of angiogenesis. Thus, it is an interesting pathway to target in combination with chemotherapies or immunotherapies. This review manuscript explores the effect of the BMP9–ALK1 pathway in tumor angiogenesis and the possible usefulness of targeting this pathway in anti-angiogenesis, vascular normalization or vascular promotion therapies.